Development of Android-Based Learning Media in the Characteristics of Trading Company Materials - Riski Rona Annisa; Kuswanto Kuswanto (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2022)
Abstract: The development of technology in the field of education provides opportunities in the use of android as a learning medium. Android is a device containing an operating system (open source) based on Linux which is widely used as a learning medium in the classroom to make the learning process more effective and efficient. This study aims to determine how the development of android-based learning media in the characteristics of trading company materials class XII IPS SMAN 6 Jambi City as an effort to meet the demands of the paradigm and how the level of feasibility of android-based learning media characteristics of trading company materials class XII IPS SMAN 6 Jambi City according to media experts, material experts, and students. This research was conducted at SMAN 6 Jambi City in April-May 2022. The development of android media uses the 4D (Define, Design, Develop, and Disseminate method. The research data was obtained using observation questionnaires to teachers in the field of economic studies as well as students, media experts and material experts. The results showed that android-based learning media material characteristics of trading companies for class XII IPS SMAN 6 Jambi City based on the assessment of media experts, material experts, teachers, and students were declared eligible or valid by obtaining a score of 119 ("very good" category) by material experts; a score of 92 (â€œgoodâ€ category) by media experts; and a score of 116 or an average percentage of 97% (category "very good") based on student response questionnaires. From the results of this study, it is suggested that: (1) Students can use their cellphones more often for learning activities compared to other entertainment activities; (2) Teachers can use android-based learning media more often if there are limitations of learning media provided by the school; (3) Schools can further equip innovative or technology-based learning media facilities for economic learning; and (4) other researchers can test the effectiveness of this media on learning.Keywords: Android Media Development, Characteristics of Trading CompaniesÂ Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana pengembangan media pembelajaran berbasis android materi karakteristik perusahaan dagang kelas XII IPS SMAN 6 Kota Jambi sebagai upaya pemenuhan tuntutan pardigma serta bagaimana tingkat kelayakan media pembelajaran berbasis android materi karakteristik perusahaan dagang kelas XII IPS SMAN 6 Kota Jambi menurut ahli media, ahli materi, dan peserta didik. Penelitian ini dilakukan di SMAN 6 Kota Jambi pada April-Mei 2022.Â  Data penelitian diperoleh dengan angket observasi terhadap guru bidang studi ekonomi serta siswa, memberikan lembar validasi kepada ahli media ahli materiÂ  dan menyebarkan angket respon siswa. Setelah itu masing-masing data dianalisis baik secara kualitatif ataupun kuantitatif.Â  Hasil penelitian menunjukkan bahwa media android sebagai upaya pemenuhan tuntutan pardigma telah berhasil dikembangkan dengan mengadaptasi model pengembangan 4D Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan) dan Disseminate (Penyebaran) menggunakan beberapa yakni; software Java Runtime Environment (JRE), Powerpoint, iSpring Suite, dan Website 2 APK Builder Pro. Untuk kelayakan media pembelajaran berbasis android materi karakteristik perusahaan dagang kelas XII IPS SMAN 6 Kota Jambi ahli media, ahli materi, guru, dan peserta didik dinyatakan layak atau valid dengan memperoleh skor 119 (kategori â€œsangat baikâ€) oleh ahli materi; skor 92 (kategori â€œbaikâ€) oleh ahli media; dan skor 116 atau persentase rata-rata 97% (kategori â€œsangat baikâ€) berdasarkan angket respon peserta didik. Dari hasil penelitian ini disarankan agar: (1) Peserta didik dapat lebih sering memanfaatkan handphone yang dipunyai untuk kegiatan pembelajaran dibandingkan kegiatan hiburan lainnya; (2) Guru dapat lebih sering memanfaatkan media pembelajaran berbasis android jika terjadi keterbatasan media pembelajaran yang disediakan oleh pihak sekolah; (3) Bagi sekolah dapat lebih melengkapi fasilitas media pembelajaran yang inovatif atau berbasis teknologi untuk pembelajaran ekonomi; dan (4) Bagi peneliti lain dapat menguji efektivitas media ini terhadap pembelajaran.Keywords: Pengembangan media android, karakteristik perusahaan dagang